Procesual approach to health behaviour of Ralf Schwarzer (part of model) as a trial of explanation of prenatal negligence - Wójcik, Wioletta (Studia Psychologica: Theoria et praxis, 2009)
The following article is focused on problem of prenatal negligence. The author defines prenatal negligence as that kind of woman behaviour which leads to injuries of fetus and threatens it’s health or life. The aim of following research is to contour the character of a phenomenon, it’s peculiarity and possible psychosocial determinants based on Ralf Schwarzer’s theories. The recognition of prenatal negligence may be helpful in reducing the problem of that phenomenon.